2021
DOI: 10.1108/jadee-07-2021-0188
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and agri-food value chain: a systematic review and bibliometric mapping

Abstract: PurposeThe COVID-19 has had a diversified and dynamic impact on the food and agricultural sector, particularly in the agri-food value chain. Although a good number of articles were published in various countries and continents covering various aspects of the impact of COVID-19 on the agri-food value chain, no significant studies were found related to the mapping of published literature to know about the scenario and current trend research. The study aims to perform a systematic review and bibliographic mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 65 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Empirical evidence indicates that the proportion of food-insecure households has increased during the pandemic due to the loss of jobs and livelihood opportunities amongst the poor and vulnerable sections of the society (Arndt et al ., 2020; Workie et al ., 2020; Kansiime et al ., 2021). The scientific community responded promptly by investing the implications of the COVID-19 pandemic on food security globally (Reardon et al ., 2020; Das and Roy, 2021; Kumar et al ., 2021; Suresh et al ., 2022). Figure 1 depicts the number of scientific publications on COVID-19 and food security during the last three years based on search data from Scopus.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical evidence indicates that the proportion of food-insecure households has increased during the pandemic due to the loss of jobs and livelihood opportunities amongst the poor and vulnerable sections of the society (Arndt et al ., 2020; Workie et al ., 2020; Kansiime et al ., 2021). The scientific community responded promptly by investing the implications of the COVID-19 pandemic on food security globally (Reardon et al ., 2020; Das and Roy, 2021; Kumar et al ., 2021; Suresh et al ., 2022). Figure 1 depicts the number of scientific publications on COVID-19 and food security during the last three years based on search data from Scopus.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the huge jump in the knowledge body of literature on COVID-19-related research and, at the same time, the existence of unknown knowledge on the implications of COVID-19, a number of studies have attempted to analyse the overall pattern of COVID-19 research investigation in society (ElHawary et al ., 2020; Gong et al ., 2020; Kaya and Erbay, 2020; Yu et al ., 2020; Wang and Tian, 2021). There is specific research on the implications of COVID-19 on various segments of life, such as entrepreneurship (Xu et al ., 2021), economics and business (Açikgöz and Günay, 2020; Verma and Gustafsson, 2020; Chandra et al ., 2021), the agri-food supply chain (Sharma et al ., 2020; Barbosa, 2021; Das and Roy, 2021) and agricultural production and food security (Okolie and Ogundeji, 2022; Ohlan and Ohlan, 2022).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Arndt et al (2020) reported that COVID-19 induced income shocks affected the livelihoods of people severely, especially in developing countries with limited economic resources and social security systems. The COVID-19 pandemic has also negatively affected the functioning of food markets by disturbing the supply chain of perishable food commodities (Das and Roy, 2021;Laborde et al, 2020). Therefore, the unavailability of perishable commodities in the markets can also be a reason for the reduction in the consumption of perishable food commodities.…”
Section: Discussionmentioning
confidence: 99%
“…Zyoud et al (2022) found that studies related to clinical research were the most frequent. Other very recent bibliometric analyses regarding COVID-19 focused on topics such as: business and management (Verma and Gustafsson, 2020); supply chains (Fabeil et al, 2023); agrifood chains (Das and Roy, 2022); nutrition (Zyoud et al, 2022); tourism (Viana-Lora and Nel-lo-Andreu, 2022); agricultural production and food security (Okolie and Ogundeji, 2022); social sciences (Singh and Verma, 2022); education (Zhang et al, 2022); and nanotechnology (Lunardi et al, 2022). Despite the availability of previous reviews, there are, to our knowledge, no publications that address the topic of farmers.…”
Section: Introductionmentioning
confidence: 99%